A sensitivity analysis on the production of potable water, green hydrogen and derivatives from South-West African seawater - Van Zyl, Shane David (Stellenbosch : Stellenbosch University, 2025)
van Zyl, S. D. 2025. A Sensitivity Analysis on the production of Potable Water, Green Hydrogen and Derivatives from South-West African Seawater. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/6ed82ebd-be0f-4b40-832a-acb904c5a763